Application of diffusion kurtosis imaging in neonatal brain development - Wang, Xueyuan; Liu, Xianglong; Cheng, Meiying; Xuan, Desheng; Zhao, Xin; Zhang, Xiaoan (Frontiers in Pediatrics, 2023)
Background: Deviating from the regular pattern of growth and development is considered to be the basis of many early childhood diseases. Therefore, it is crucial to describe the early brain development. This study aims to explore the change patterns of white matter and gray matter during neonatal brain development using DKI. Materials and Methods: 42 full-term neonates were investigated by brain conventional MRI and DKI. The DKI metrics of white matter and deep gray matter were measured. DKI metrics from the different ROIs were interrogated with Kruskal-Wallis test and Bonferroni method. The Spearman rank correlation analysis of the DKI metrics and the age at the time of brain MRI acquisition was calculated. Finally, all subjects were divided into three groups according to the age at the time of brain MRI acquisition. Results: MK, Ka, Kr and FA values showed positive correlations with the age at the time of brain MRI acquisition, MD, Da and Dr values correlated negatively with the age at the time of brain MRI acquisition. The absolute correlation coefficients between MK values of almost all ROIs and the age were greater than other metrics. The kurtosis parameters and FA values of central white matter were significantly higher than that of peripheral white matter. The kurtosis parameters and FA values of globus pallidus and thalamus were significantly higher than caudate nucleus and putamen. The relative change rates of kurtosis parameters and FA values of all ROIs were greater than that of MD, Da and Dr values. The amplitude of MK values of almost all ROIs was greater than other metrics. Conclusion: DKI parameters showed the potential advantage in detecting the changes of brain microstructure during neonatal brain development. The range and degree of DKI metrics changes in neonatal white matter and gray matter were different, which reflected the heterogeneity of tissue microstructure and the typical developmental characteristics. The changes of MK value were the most obvious in both white matter and gray matter.